Ideology, patronage, and manipulation of translation in Zouxiang weilai congshu: With special reference to the translation and introduction of Max Weber - Cui, Feng (Frontiers in Communication, 2022)
Cultural Studies helps us to see that translation is not merely a simple and isolated process but is intricately bound to ideology, patronage, and poetics. Through the study of translated texts, we can explore power relations, and this has the potential to reflect such power structures within a wider cultural context. This paper examines 走向未来丛书 (Zouxiang weilai congshu), literally “Toward the Future Book Series,” and focuses on its selection and introduction of western texts and its interaction with Chinese ideological trends, to explore the relationship between translation and politics in the 1980s, focusing on discussing the translation and introduction of Max Weber. Current studies of Max Weber largely focus on Weber's thought, while the few that touched upon translation in China were merely brief descriptions lacking deep analysis. Moreover, there have not been any papers which place Weber in historical and cultural context to explore the interaction between translation and politics. This paper employs a different approach where the focus is placed on the series' translation of Weber and the social ideology behind the translation. Not only does it unearth the influence of publishers' and patron's identities on the act of translation, but it also reflects on the role of the editorial board's unique mode of operation in the translation process. The case study of this paper not only focuses on diachronic translation activities, but is also concerned with the cultural space in which translation events occurs, translators' cultural objectives of translating, as well as foreign authors who enter the cultural context where the target language is used. By placing translated literature against a specific cultural time and space, this paper explains the cultural objectives and forms of literary translation, as well as translations that were specially made to achieve certain cultural objectives and the cultural effect of such translations.